Challenges in COVID-19 in Patients with Haematological Malignancies: Case Report of a Patient with Mantle Cell Lymphoma - Knorz, Sebastian; Wiebecke, Susanne; Schulze, Petra; Schimanski, Sven; Strifler, Susanne; Gassenmaier, Tobias; Klinker, Erdwine; Weissbrich, Benedikt; Klinker, Hartwig (Archives of Clinical and Medical Case Reports, 2021)
Introduction: Patients with haematological malignancies after chemotherapy are immunocompromised and therefore highly susceptible to Covid-19 disease. Case presentation: The case report presents a patient with mantel cell lymphoma who experienced a severe Covid-19 disease. Simultaneously, a pulmonary thromboembolism and a cerebral bleeding were detected, thereafter a cytomegalovirus reactivation. A therapy with convalescent plasma showed just an intermediate effect on the patient´s prolonged positivity for SARS-CoV-2. Conclusion: The management of COVID-19 disease in patients with haematological malignancies is a complex challenge due to the diverse impairment of the immune system. In addition to the underlying disease, opportunistic infections are of great relevance.